The Role of Islamic Religious Education in Cultivating Religious Moderation Among Digital Youth - Fachrurazi, Fachrurazi (PT. Anagata Sembagi Education, 2025)
The development of digital technology has changed the way adolescents access and understand religious teachings. Amidst the rapid flow of unverified information, Islamic Religious Education (PAI) plays a strategic role in shaping moderate character among digital youth. This study aims to analyze the role of PAI in fostering religious moderation, with a focus on learning strategies, the role of teachers, the use of digital media, as well as the challenges and solutions to its implementation. The study was conducted using a qualitative approach through case studies at MAN 1 and MAN 2 Sragen, using in-depth interviews, participant observation, and document analysis. The results show that the PAI curriculum in both madrasas has been integrated with moderate values ​​such as tolerance, social justice, and respect for differences. PAI teachers play a crucial role as facilitators and agents of change, while the use of digital technology has proven effective in increasing students' interest in learning about contemporary religious issues. Students who participated in moderation-based PAI learning showed significant improvements in religious digital literacy, tolerance, and the ability to engage in dialogue amidst diversity. Challenges such as low teacher digital literacy and the negative influence of social media still need to be addressed through ongoing training and collaboration with various parties. This finding strengthens the position of Islamic Religious Education as a transformative instrument in forming a young generation that is religious, inclusive, and adaptive to social and technological dynamics